Feeding, milking and manure systems in Estonian dairy barns - Helis Luik; Ans-Hannes Viira (Agraarteadus, 2016)

(untitled)
In 2012, a farm survey was carried out by the Institute of Economics and Social Sciences of the Estonian University of Life Sciences that aimed to gather the information about the technologies that Estonian dairy farms use. Studying the technological solutions used in dairy farms is relevant, because dairy farms contribute significantly to the Estonian agricultural output, and utilise remarkable amount of resources. Modern technology is one of the key drivers of productivity growth in a sustainable way. Therefore, understanding the current technological level of the dairy farms, and seeking for the needs for technological improve-ment, contributes to developing the policies that address the sustainability of the dairy sector. The paper surveys the technologies used in specialised Estonian dairy farms in 2012, therefore contributing the first overview of the technologies used in Estonian dairy farms since the EU accession. The paper reviews the following technological indicators: the number and type of dairy barns in the farm; the number of places for dairy cows in the barn; the year of construction or reconstruction of the barns and technological systems; milking technology; milking frequency; feeding systems; manure systems. The survey revealed that the significant technological change in dairy farms started in 2001. Since then, most of the barns that are built are uninsulated, feeding and milking technologies are upgraded, and manure systems are changed to liquid systems. At the same time, there is still a remarkable technological gap between smaller and larger dairy farms.